PENGEMBANGAN MEDIA PEMBELAJARAN GOOGLE SITES DENGAN MODEL ADDIE - Juwariyah, Juwariyah; Fatirul, Achmad Noor; Waluyo, Djoko Adi (Edutech (Kecamatan Padang Sidempuan Selatan dalam angka), 2025)
This study aims to develop Google Sites learning media with the ADDIE model in the subject of non-conventional machining engineering for grade XII students of SMK PGRI 1 Gresik. By using the ADDIE development model and combining qualitative data analysis techniques in the form of suggestions for improvement and quantitative data obtained from the questionnaire for assessing the feasibility of learning media by test subjects, this Google Sites learning media is suitable for use in vocational high school learning by going through several stages of validity and feasibility tests. The results of the product feasibility based on the results of the validation of material experts showed a final value of 96% in the very feasible category. The assessment of the design expert validation showed a final value of 89% in the feasible category. The assessment of the media expert validation showed a final value of 88% in the feasible category. The results of peer validation showed a final value of 93% in the very feasible category and the results of field trials consisting of individual trials obtained 92.5% in the very feasible category, small group tests obtained 91.3% in the very feasible category, and large group tests obtained 92.5% in the very feasible category. This shows that the Google Sites learning media can help and facilitate teachers in presenting non-conventional machining technique teaching materials for the learning objective of operating the GSK 281 mCH CNC Milling machine, in addition, students find it easy to use this Google Sites media and help smooth the learning process of class XII students of Machining Engineering at SMK PGRI 1 Gresik.Tujuan penelitian ini untuk mengembangkan media pembelajaran google sites dengan model ADDIE pada mata pelajaran teknik pemesinan non konvensional siswa kelas XII SMK PGRI 1 Gresik. Dengan menggunakan model pengembangan ADDIE dan menggabungkan teknik analisis data kualitatif berupa saran perbaikan dan data kuantitatif yang diperoleh dari angket penilaian kelayakan media pembelajaran oleh subyek uji, media pembelajaran google sites ini layak digunakan pada pembelajaran SMK dengan melalui beberapa tahapan uji kevalidan dan kelayakan. Hasil dari kelayakan produk berdasarkan hasil dari validasi ahli materi menunjukkan nilai akhir 96% kategori sangat layak. Penilaian dari validasi ahli desain menunjukkan nilai akhir 89% kategori layak dan perlu revisi. Penilaian dari validasi ahli media menunjukkan nilai akhir 88% kategori layak dan perlu revisi. Hasil dari validasi teman sejawat menunjukkan nilai akhir 93% dengan kategori sangat layak dan hasil uji coba lapangan yang  terdiri dari uji coba perorangan diperoleh 92,5% kategori sangat layak, uji kelompok kecil diperoleh 91,3% kategori sangat layak, dan uji kelompok besar diperoleh 92,5% kategori sangat layak. Hal ini menunjukkan bahwa media pembelajaran google sites ini dapat membantu dan memudahkan guru dalam menyajikan materi ajar teknik pemesinan non konvensional pada tujuan pembelajaran mengoperasikan mesin CNC Milling GSK 281 mCH, selain itu peserta didik merasa mudah dalam menggunakan media google sites ini dan membantu memperlancar proses kegiatan belajar peserta didik kelas XII Teknik Pemesinan di SMK PGRI 1 Gresik.